Scaffolding Turkish EFL Students’ Grammar Learning Experiences through Output Activities - Kufi, Elmaziye Ozgur (Fırat University, 2023)
Students in EFL contexts have limited opportunities for using English productively in communicative activities. Based on this concern, the present study initiated the use of output activities in an evening course in Northern Cyprus and aimed to explore whether their use enhances effective use of grammatical structures by learners. To find out whether the use of output activities leads to any significant improvement in the use of grammatical forms, participating students were asked to write two compositions, one before participating in output activities and another one afterwards. Questionnaires were also administered to elicit teachers’ and students’ perceptions related to their grammar teaching and learning experiences respectively. Collected data were analyzed using qualitative and quantitative methodology since the study had an exploratory mixed method research design. Comparison of the analyzed data from learners’ first and second compositions revealed that learners could use grammatical structures more successfully in their second compositions. Likewise, analysis of qualitative and quantitative data collected through questionnaires disclosed positive student and teacher perceptions regarding the use of output activities in the language course. Consequently, based on its positive results, the current study suggests integration of output activities into foreign language teaching practices and curricula for scaffolding students’ grammar learning experiences.
Keywords: Other Fields of Education; Alan Eğitimleri